CRF receptor type 1 (but not type 2) located within the amygdala plays a role in the modulation of anxiety in mice exposed to the elevated plus maze - Cipriano, Ana Cláudia [UNESP]; Gomes, Karina Santos [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2016)
The amygdala (Amy) is an important center that processes threatening stimuli. Among the neurotransmitters implicated in the control of emotional states, the corticotrophin releasing factor (CRF) is an important modulator, acting at CRF1 and CRF2 receptors. Few studies have investigated the role of CRF and its receptors in the Amy on anxiety in mice. Here, we investigated the effects of intra-Amy (aimed at the basolateral nucleus) injections of CRF (37.5 and 75 pmol/0.1 μl), urocortin 3 (UCn3, a selective CRF2 agonist; 4, 8, 16 or 24 pmol/0.1 μl), CP376395 (a selective CRF1 antagonist; 0.375, 0.75 or 1.5 nmol/0.1 μl), antisauvagine-30 (ASV-30, a selective CRF2 antagonist; 1 or 3 nmol/0.1 μl) on the behavior of mice exposed to the elevated plus maze (EPM). Both spatiotemporal (e.g., percentage of open-arm entries and percentage of open-arm time; %OE and %OT) and complementary [e.g., frequency of protected and unprotected stretched attend postures (pSAP and uSAP) and head dips (pHD and uHD); frequency and time spent on open arm end exploration (OAEE)] measures were recorded during a 5-min test in the EPM. While intra-Amy injections of CRF decreased %OE, %OT and OAEE, suggesting an anxiogenic-like action, UCn3 (all doses) did not change any behavior. In contrast, injections of CP376395 (0.75 nmol) produced an anxiolytic-like effect, by increasing %OT and OAEE and decreasing pSAP and pHD. Neither spatiotemporal nor complementary measures were changed by intra-Amy ASV-30. These results suggest that CRF plays a marked anxiogenic role at CRF1 receptors in the amygdala of mice exposed to the EPM.
Keywords: Amygdala; Anxiety; Corticotrophin releasing factor; CRF1 and CRF2 receptors; Elevated plus maze; Mice